New host records and a checklist of fishes infected with Austrodiplostomum compactum (Digenea: Diplostomidae) in Brazil - Ramos, Igor Paiva [UNESP]; Franceschini, Lidiane [UNESP]; Zago, Aline Cristina [UNESP]; Penha Zica, Erica de Oliveira [UNESP]; Wunderlich, Alison Carlos [UNESP]; Carvalho, Edmir Daniel [UNESP]; Silva, Reinaldo Jose da [UNESP] (Brazilian Coll Veterinary Parasitology, 2013)
This study reports the infection of fishes by Austrodiplostomum compactum metacercariae in the Chavantes reservoir, medium Paranapanema River, municipality of Ipaussu, Sao Paulo State, Brazil. Twenty-three fish species were analysed, and 13 were infected with A. compactum metacercariae (56.5%) in their eyes. The following six fish species are new hosts for this metacercaria: Crenicichla haroldoi (1/1), Eigenmannia trilineata (11/6), Hoplosternum littorale (11/1), Iheringichthys labrosus (17/2), Leporinus amblyrhynchus (11/1), and Piaractus mesopotamicus (3/1). These new species increase the number of Brazilian fish species infected with this parasite to 36. Based on these findings, we hypothesise that the metacercariae larval stage of the parasite has a low specificity for the second intermediate host (fish). The majority of fish species infected in Brazil belong to the Loricariidae and Cichlidae families. For the fish species with higher mean abundances in Brazil, six are non-native species, and currently, Plagioscion squamosissimus has the highest mean abundance. The majority of fish species infected with A. compactum in Brazil are concentrated in the Parana basin, although this may be related to the distribution of researchers.
Keywords: Freshwater fishes; parasite; Trematoda; metacercariae; infection; Parana basin